Evaluating the effectiveness of gabapentin and ginkgo biloba in the neuroinflammatory process within a co-culture model of GBM and neurons - Sevim, Çiğdem; Taghizadehghalehjoughi, Ali (Hacettepe University, 2025)
This study aimed to investigate the anti-inflammatory effects of Ginkgo Biloba extract and Gabapentin on a neuron-Glioblastoma cell line. Utilizing advanced co-culture techniques, we simulated a tumor environment that closely mimics in vivo conditions and performed a detailed genetic analysis of cytokine expression. Testing a range of doses from 20 to 80 µg/ml, we found that the combination of Gabapentin (80 µg/ml) and Ginkgo Biloba extract (80 µg/ml) did not alter levels of proinflammatory cytokines such as IL1β, IL6, IL8, and TNF-α. However, it significantly increased the levels of the anti-inflammatory cytokine IL10 compared to other groups. These findings suggest that the co-administration of Gabapentin and Ginkgo Biloba can modulate the inflammatory response, maintaining it at levels similar to the control group. Determining the precise effective dosage range and understanding the mechanisms to halt neuroinflammation will be crucial for advancing therapeutic options for glioblastoma multiforme. This research provides a promising foundation for developing new treatment strategies aimed at reducing inflammation in glioblastoma patients.
Keywords: Cell culture; Proinflammatory cytokines; Glioblastoma multiforme; Interleukin; hücre kültürü; proinflamatuar sitokin; glioblastoma multiforme; interlökin; Proinflammatory cytokines; Gene Expression; Cell culture; Interleukin; Gen İfadesi; Glioblastoma multiforme